2011
DOI: 10.1091/mbc.e11-05-0391
|View full text |Cite
|
Sign up to set email alerts
|

Knock-in reconstitution studies reveal an unexpected role of Cys-65 in regulating APE1/Ref-1 subcellular trafficking and function

Abstract: The multifunctional APE1 protein is required for tumor progression and is associated with cancer resistance. It is shown that APE1 presents structural elements that function in distinct cellular roles, highlighting the molecular determinants of the multifunctional nature of this protein and providing the basis for a new role of the C65 residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 77 publications
(155 reference statements)
8
81
0
Order By: Relevance
“…Although the KD cells eventually die, exhibiting the typical growth arrest and apoptosis, this model has been a valuable tool for delineating the contribution of specific APE1 functions. Consistent with the previous work, KD cells complemented with a nuclease-deficient human APE1 cDNA harboring an H309N mutation did not survive, confirming the essential nature of the DNA repair activities of the enzyme (213). However, in contrast to what the Mitra laboratory observed (see above), the C65S redox regulatory mutant did not rescue the inviability of the KD cells; whereas the non-acetylatable K6R/K7R mutant provided near wild-type complementation for cell growth.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Although the KD cells eventually die, exhibiting the typical growth arrest and apoptosis, this model has been a valuable tool for delineating the contribution of specific APE1 functions. Consistent with the previous work, KD cells complemented with a nuclease-deficient human APE1 cDNA harboring an H309N mutation did not survive, confirming the essential nature of the DNA repair activities of the enzyme (213). However, in contrast to what the Mitra laboratory observed (see above), the C65S redox regulatory mutant did not rescue the inviability of the KD cells; whereas the non-acetylatable K6R/K7R mutant provided near wild-type complementation for cell growth.…”
supporting
confidence: 84%
“…Moreover, a recent study found that full-length APE1 resides mainly in the mitochondrial intermembrane space (213), a localization pattern that appears distinct from other mtBER proteins, which are associated with mtDNA in the matrix (198). In this work (213), APE1 was shown to interact, in a proximity ligation assay, with the oxidoreductase Mia40, which plays a key role in oxidative protein folding within the mitochondrial inter-membrane space. Thus, the current data suggest a model in which a presently unknown PTM of full-length APE1 is necessary to reveal the ''masked'' MTS within the C-terminus and enable mitochondrial-specific protein interactions that direct mitochondrial localization.…”
Section: Intra-cellular Targeting and Mitochondrial Functionmentioning
confidence: 58%
See 3 more Smart Citations